Unconditional quantile regressions, earnings disparity and gender discrimination in post-transformation of urban China - Tang, Yao; Long, Wenjin (2012)
Market-oriented economic reform has gone through several key stages to bring substantial changes to current Chinese economy. It has accelerated after 1992, and meets the pattern transformation of economic development in 2002. During this dramatic and complicated economic transitional process, some issues caused people’s attention included the questions as: how does the earnings distribution change between genders from early market economy to post market economy; how do education, work experience, marriage and other factors affect gender earnings and what is the difference in internal group of women. In this paper, it will be used the data of the Chinese household income projects in 2002 and 2007 to analyse earnings disparity between genders and inner woman group. The unconditional quantile regression finds that comparing with past, the negative effect on earnings of marriage and taking care of child has much decreased, especially to women. However, high return rate to education of female workers is not as significant as before, the rate of work experience even fall faster. Along with the gender earnings gap increasing, the unexplained gap (discrimination gap) also increased over time, and is particularly pronounced for the lower and higher earnings group of women.